Global trends in Akkermansia muciniphila research: A bibliometric visualization - Li, Zitong; Ke, Haoran; Wang, Ying; Chen, Shuze; Liu, Xiuying; Lin, Qianyun; Wang, Pu; Chen, Ye (Frontiers in Microbiology, 2022)
Background: Akkermansia muciniphila is a member of the gut microbiome, using mucin as sources of carbon, nitrogen, and energy. Since the first discovery of this unique bacterium in 2004, A. muciniphila has been extensively studied. It is considered as a promising “next-generation beneficial microbe”. The purpose of this paper is to sort out the research status and summarize the hotspots through bibliometric analysis of the publications of A. muciniphila. Methods: The publications about A. muciniphila from January 2004 to February 2022 were from the Web of Science Core Collection. And then visualization analyses were performed using three bibliometric tools and GraphPad Prism. Results: A total of 1478 published documents were analyzed. Annual publication number grew from 1 in 2004 to 336 in 2021, with China being the leading producer (33.36%). De Vos, Willem M was the most productive author with the highest H-index (documents=56, H-index=37), followed by Cani, Patrice D (documents=35, H-index=25). And Scientific Reports published the most papers. PANS was keystone taxa in this field for having high betweenness centrality (0.11) and high frequency. The keywords with high frequency in recent years include: oxidative stress, diet, metformin, fecal microbiota transplantation, short-chain fatty acids, polyphenols, microbiota metabolites and so on. Interestingly, “oxidative stress” was observed to be increasing recently. Conclusions: Over time, the scope of the research on the clinical uses of A. muciniphila gradually increased, and the contents were gradually deepened and developed towards a more precise level. A. muciniphila is likely to remain a research hotspot in the foreseeable future and contributes to human health.